2011
DOI: 10.5146/tjpath.2010.01045
|View full text |Cite
|
Sign up to set email alerts
|

P53, bcl-2, and nm23 expressions in serous ovarian tumors: correlation with the clinical and histopathological parameters

Abstract: The p53 positivity detected only in serous carcinomas shows its role in carcinogenesis. p53 was expressed at a significantly higher rate in advanced stage carcinomas (p = 0.031). nm23 expression in benign, borderline and malignant tumors was not significantly different. nm23 positivity was higher in advanced stage carcinomas (p = 0.032). This suggest that nm23 acts like an oncogene in ovarian carcinomas. There was no significant difference between the groups in terms of bcl-2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
2
9
0
2
Order By: Relevance
“…from 29 to 40.7% [1,5,6,7,8,9,12,13], and a small number of studies showed higher rates of CIN2/CIN3 for LSIL/ASC-H, i.e. from 45 to 61% [2,3,4]. Our result was 43%, which is consistent with the former results.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…from 29 to 40.7% [1,5,6,7,8,9,12,13], and a small number of studies showed higher rates of CIN2/CIN3 for LSIL/ASC-H, i.e. from 45 to 61% [2,3,4]. Our result was 43%, which is consistent with the former results.…”
Section: Discussionsupporting
confidence: 82%
“…In line with these studies, our results support that the current clinical practice is valid (management is the same for ASC-H) [3,4,6,9,13]. …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations